Consumo de alcohol y sustancias psicoactivas en adolescentes mestizos e indígenas del cantón El Pangui y Centinela del Cóndor de la provincia de Zamora Chinchipe. - Ortiz Cochancela, Rubén Dario (2016)
This research called “alcohol and psychoactive substances” in mestizos as well as indigenous adolescents in El Pangui and Sentinel Condor, both cities from the province of Zamora Chinchipe, was made in order to get to know in what grade adolescents make this act. As it has been a problematic of our whole society and it has become one of the main factors of death and personal conflicts worldwide. This research work is an epidemiological, descriptive and a transversal study, so the applied instrument was a semi-structured survey, by taking into account the survey of the technical secretariat of drugs with changes in its variables. The sample included 412 students, where a high consumption as alcohol as well some other kinds of psychoactive substances was evident.Most students consume alcohol or some kind of psychoactive substance, being alcohol the most prevalent; followed by marijuana, inhalants and base, whereas it is shown that alcohol consumption is initiated by curiosity, producing or maintaining this consumption either by family problems, pressure or peer group acceptance and interpersonal conflicts. In the same way it was noted that alcohol consumption is similar in both men and women presenting a higher prevalence of first use of this substance at 13 and 14 correspondingly. Concerning psychoactive substances consumption, it is higher in men and consumer ages of onset ranging at 12 and it varies according to the type of substance. Considering the Shuar nationality, the results showed that alcohol and psychoactive substances consumption is majority in men except plant drugs whereas it was determined that women have a higher consumption.